KH. Abdurrahman Wahid: Telaah Pemikiran Dan Relevansinya Pada Pendidikan Multikultural di Indonesia - Lathif, Wardil; Alimul Muniroh (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2023)
Multicultural Education is an alternative means of conflict resolution, students are expected not to leave their cultural roots. Multicultural education is very relevant to use for existing democracy as it is today ic accordance with KH. Abdurrahman Wahid’s thoughts. Abdurrahman Wahid who supports democratic values. This study aims to explore KH. Abdurrahman Wahid’s thought and it relevance to Multicultural Education in Indonesia. Design of study is library research (library research). Data of the study were based on works of KH. Abdurrahman Wahid. The result of study on KH. Abdurrahman Wahid thought, showed that the differences in religion, culture, and ethnicity to be addressed wisely; every group ini society has an equal position; Islam recognizes the existence of differences in religion; Plurality in the world is a reality. The relevance of KH. Abdurrahman Wahid with Multicultural Education in Indonesia, namely: showed that the differences in religion, culture, and ethnicity to be addressed wisely relevant to the system, process, evaluation, goals of multicultural education; Every group ini society has an equal position is relevant to the evaluation of multicultural education; Islam recognizes the existence of differences in religion relevant to the goals of multicultural education; Plurality in the world is a reality relevant to the multicultural education system.